Immunohistochemical expression of Ki67, EGFR and TRKC and their correlation with prognostic factors in medulloblastoma - Ana Cristina Lira Sobral; Victor Moreschi Neto; Gabriela Traiano; Jeana Rosales; Luana E. Harada; Ana Paula Percicote; Elizabeth Schneider Gugelmin; Lúcia de Noronha (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Medulloblastoma is a malignant embryonal tumor of the cerebellum with poor prognosis. The treatment is based only on clinical criteria, such as risk group that only considers age, extent of tumor resection, recurrence, and metastasis. Objective: To evaluate a possible relationship between the immunoexpression of biomarkers (Ki67, receptor neutrophin-3 [TRKC], epidermal growth factor receptor [EGFR], B-cell lymphoma 2 [Bcl-2], and cyclin-D1), and the classical clinical prognostic factors of medulloblastoma. Material and method: thirty-five samples of pediatric medulloblastoma free of neoadjuvant chemotherapy were separated and reviewed for their histopathological classification; two areas representative of tumor were used in the construction of tissue microarrays. The following clinical data from 29 patients were used for comparison with the biomarkers expression: patient's age, presence or absence of complete tumor resection, staging patient's risk group, presence or absence of metastases, presence or absence of postoperative chemotherapy, and presence or absence of recurrence. Clinical follow-up of the study ranged from two to thirteen years, and cases with fatal outcome were also analyzed. Results: Patients with upper age showed higher expression of TRKC (p = 0.033). There was inversely proportional and statistically significant correlation between TRKC and Ki67 (p = 0.027). There was no statistical significance in the analysis of EGFR, Bcl2, and cyclin-D1. Conclusion: The immunoexpression of TRKC might be considered a biomarker related to tumors with better prognosis in patients with medulloblastoma, contributing to better risk groups' stratification.